Accessibility within open educational resources and practices for disabled learners: a systematic literature review - Zhang, Xiangling; Tlili, Ahmed; Nascimbeni, Fabio; Burgos, Daniel; Huang, Ronghuai; Chang, Ting-Wen; Jemni, Mohamed; Khribi, Mohamed Koutheaïr (Smart Learning Environments, 2020)
The number of disabled students is rapidly increasing worldwide, but many schools and universities have failed to keep up with their learning needs. Consequently, large numbers of disabled students are dropping out of school or university. Open Educational Resources (OER) and Open Educational Practices (OEP) contain several relevant features, including the possibility of reusing and remixing, which have led researchers to consider using OER and OEP to facilitate meeting the needs of disabled and functional-diverse students in order to increase their accessibility and e-inclusion capabilities in educational settings. The very limited research to date, however, has provided a limited holistic understanding of accessibility within OER and OEP in order to aid researchers in pursuing future directions in this field. Therefore, this paper systematically reviewed 31 papers to provide insights about functional diversity within OER and OEP. The results obtained highlighted that accessibility is still in its infancy within OER and that researchers should focus more on considering the four accessibility principles — perceivable, operable, understandable and robust — when providing OER. Additionally, while several researchers have focused on several issues related to accessibility within OER, limited focus has been given to assistive technologies using OER. Finally, this paper provides several recommendations to increase accessibility within OER and help design more accessible OER for students with functional diversity.
Keywords: accessibility; disability; inclusion; open educational practices; open educational resources; Scopus; Emerging